Обеспечение помехозащищенности в системах передачи при использовании двумерных оптических направляющих структур на основе фотонных кристаллов - Филипенко, А. И.; Донсков, А. Н. (Харьковский национальный университет радиоэлектроники, 2015)
We investigated the impact of the pillars diameter on the frequency band in the case of 2D photonic crystal guide. We also have shown that by changing the diameter of some pillars in the photonic crystal waveguide structure we can design filters with various characteristics.
Keywords: электромагнитная совместимость; фотонные кристаллы; помехозащищенность; системы передачи; двумерные оптические структуры